On Nash equilibrium in prices in an oligopolistic market with demand characterized by a nested multinomial logit model and multiproduct firm as nest - Gang Liu (Statistics Norway, Research Department, 2006)
This note provides a proof on existence and uniqueness of Nash equilibrium in prices in a market where the demand side is characterized by a nested multinomial logit model with multiproduct firm as nest and the supply side consists of oligopolistic price-setting multiproduct firms with each producing various differentiated variants.
Keywords: C25; C62; C72; D43; L13; 330; oligopolistic market; multiproduct firm; nested multinomial logit model; Nash equilibrium